Violent conflicts in ARMM: Probing the factors related to local political, identity, and shadow-economy hostilities - Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2017)
The Philippines has a long history of internecine warfare or conflicts, especially in Mindanao where the secessionist conflicts alone since the 1970s have resulted in enormous human and economic costs. That violent social discords remain varied and widespread in Mindanao underscores the need for a better understanding of their causes to guide policy. Applying regression analysis on a panel dataset for 2011-2014, we examine the factors behind the municipal- and city-level incidence of violent conflicts related to political, identity and shadow-economy issues in the Autonomous Region of Muslim Mindanao. Indicating that geography matters, we find evidence that conflicts spill over between neighboring localities, although the type of conflicts in one locality may not be same as that in its neighbors. Having many neighbors makes a locality more susceptible to political or identity conflicts, while those lying along the coast are more prone to shadow-economy conflicts. Indicating the importance of the quality of local governance, there are fewer cases of identity conflicts in localities where the mayor was re-elected, but more cases of shadow-economy and identity conflicts where the mayor and the vice-mayor or the district representative to Congress are relatives or belong to the same political clan. Also, we find the level of local government fiscal resources to be associated with lower incidence of identity conflicts, but also with higher incidence of disputes related to the underground economy. Moreover, the incidence of identity or shadow economy conflicts is higher in cities and in highly-urbanized provincial capitals than in municipalities. Finally, we find that political conflicts are indeed more frequent in 2013 (election year), and that both identity and shadow economy conflicts have become prevalent in 2014 than in 2011. These results identify some critical areas for interventions to reduce the occurrence or spread of violent discords in ARMM.
Keywords: O17; O18; R10; H77; 330; Political conflicts; identity conflicts; shadow economy; local governments; negative binomial model; Mindanao